Contribución al estudio de las algas marinas bentónicas de Punta Arena y Cabo Pulmo, Baja California Sur, México - Mateo-Cid, Luz Elena; Mendoza-González, A. Catalina; Galicia García, Citlalli; Huerta Múzquiz, Laura (Instituto de Ecología, A.C., 2000)
Benthic marine algae were collected at Punta Arena and Cabo Pulmo, Baja California Sur, México, between 1989 and 1994. The number of species found ascends to 115, 4 belonging to Cyanophyceae, 66 to Rhodophyceae, 23 to Phaeophyceae, 4 to Bacillariophyceae and 18 to Chlorophyceae. 88 species were determined from Punta Arena and 68 from Cabo Pulmo. The floristic list includes data on reproductive stages, tidal levels and exposure to surf, substratum and epiphytism. The studied algal flora is of tropical affinity and has its greatest diversity in spring. Pneophyllum conicum (E. Y. Dawson) Keats, Chamberlain et Baba, Hincksia rallsiae (Vickers) P.C. Silva and Acetabularia parvula Solms-Laubach are new records for the Gulf of California.